Sensor para análise das características físico-químicas de óleo de soja por meio da constante dielétrica - Paiter, Leandro (2015)
This paper proposes the use of a capacitive sensor for determining the dielectric constant to characterize vegetable oil samples before and after the frying process. In tests, the fry was simulated by heating oil subjected to heating and cooling cycles. From measuring the dielectric constant of the oil was made the correlation of this magnitude with the result of physical and chemical analysis. To determine the dielectric constant of the samples, two probes were constructed: a sensor i can analyze the capacitance of the samples until the maximum temperature of 120° C and the sensor analyzes II allows up to a maximum of 250 ° C. The difference between the sensors I and II is in the working temperature of the materials used in its construction. The results show that in the heating cycle, the dielectric constant of the sample and its initial value increased in the cooling curve of the decrease of the dielectric constant is different from that obtained on heating. After each complete cycle of heating and cooling, the dielectric constant value was increased, indicating a permanent change in the physicochemical properties of the samples. The verification of the permanent change was confirmed by physicochemical analysis of samples (acid value, iodine value, refractive index and viscosity) and the correlation obtained in the dielectric constant. To this was collected 10 ml of each sample analyzed. The results suggest that the dielectric constant measuring method can be rapid and economically to characterize edible vegetable oils subjected to temperature variations between 20 and 250 ° C, for example, when used for frying. The application of this simple analysis can be useful in assessing the allocation / recycling of waste vegetable oil frying processes.